Implementation of Hypertension Exercises to Lower Blood Pressure in Elderly People with Hypertension in Ikedaen Okinawa Japan - Fatikha, Jihan Natasya; Jati, Riani Pradara (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Hypertension is often referred to as the "silent killer", because hypertension sufferers often go years without experiencing any problems or symptoms. Without realizing it, hypertension sufferers experience complications in vital organs such as the heart, brain or kidneys. The aim of this research is to provide hypertension exercise therapy to reduce blood pressure in the elderly. This scientific study uses the hypertension exercise method once a day for 3 days. The results of blood pressure checks before and after applying hypertension exercises to the patient were 180/110 mmHg to 172/100 mmHg. The conclusion was that after implementing hypertension exercises for 3 days, there was a decrease in blood pressure in hypertensive patients. You should be able to carry out hypertension exercises independently to help reduce or control blood pressure.